Physical Properties and Preference Levels Testing of Perfume Formulation From Medang Pirawas Leaf’s Essential Oil (Litsea Elliptica Blume) - Handayani, Indri Astuti; Syahputra, Guritno; Rismana, Eriawan; Susanti, Yanthy (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2025)
The use of perfume is a necessity in daily life for many individuals. Perfume compositions rely on essential oils, categorized into top, middle, and base notes, which differ based on the volatility and specific gravity of the oils used. The essential oil of medang pirawas leaves (Litsea elliptica Blume), rich in terpineol (23.36%), is known for its distinct aroma and is used in perfumes. This study aimed to evaluate the physical properties and preference levels of perfume formulations made with Litsea elliptica essential oil. The oil was extracted via steam distillation and analyzed using GC-MS. A base formula (F0) combined Litsea elliptica and lavender essential oils, with variations incorporating sweet orange (F1), lemon (F2), lime (F3), and bergamot (F4) essential oils. Physical tests included specific gravity (0.7–1.2), stain tests on tissue, HVS, and filter paper, and aroma longevity (>240 minutes). Preference tests were conducted with 30 respondents. All formulations met specific gravity standards and showed no staining. F4 was the only formulation that satisfied aroma longevity requirements, while F1 was the most preferred. Statistical analysis using SPSS 26 revealed data normality for specific gravity and aroma longevity. Paired Sample T-Tests showed significant effects of citrus essential oils on specific gravity (p = 0.01) but not on aroma longevity (p = 0.638). In conclusion, the formulations met physical property standards beside aroma longevity which only F4 excelled at and F1 being the most favored by respondents. The addition of citrus essential oils had a significant impact on the specific gravity, but not for the aroma longevity.